Cross-sectional study of the dispensation of synthetic anorectic drugs in community pharmacies in the city of Cruz Alta - State of Rio Grande do Sul - Marcieli Maria Navarini; Viviane Cecilia Kessler Nunes Deuschle; Regis Augusto Norbert Deuschle (Brazilian Journal of Pharmaceutical Sciences, 2014)
Obesity is defined as the excess adipose tissue in the body. Drugs responsible for inhibiting the appetite are called anorectics or appetite suppressants. Sibutramine, fenproporex and amfepramone belongs to this class, and are capable of causing physical or psychological dependence. The aim of this study was to evaluate the frequency of prescriptions for appetite suppressants in community pharmacies at Cruz Alta, State of Rio Grande do Sul, Brazil. The sales of fenproporex, amfepramone and sibutramine in the months of September, October and November 2010 and April, May and June 2011 were compared. It was observed that the most commonly dispensed anorectic in the three community pharmacies analyzed was sibutramine. In the months of September, October and November 2010, consumption was higher, with sibutramine achieving 40.3% of overall sales, amfepramone 21% and, finally, fenproporex, 7.9%. The consumption of appetite suppressants was more prevalent in females, who represented 82% of total. The results suggested the existence of high consumption of anorectics, possibly related to the current concern with aesthetic standards, which emphasizes the importance of strict control over the marketing of these substances.